Ultrasound assessment of diaphragmatic function in patients with amyotrophic lateral sclerosis - Fantini, Riccardo; Mandrioli, Jessica; Zona, Stefano; Antenora, Federico; Iattoni, Andrea; Monelli, Marco; Fini, Nicola; Tonelli, Roberto; Clini, Enrico; Marchioni, Alessandro (Respirology (Carlton, Vic.), 2016)
Background and objective Evaluation of diaphragm function in Amyotrophic Lateral Sclerosis (ALS) is critical in determining when to commence non‐invasive mechanical ventilation (NIV). Currently, forced vital capacity (FVC) and sniff nasal inspiratory pressure (SNIP) are volitional measures for this evaluation, but require collaboration and are poorly specific. The primary aim of this study was to assess whether diaphragmatic thickness measured by ultrasound (US) correlates with lung function impairment in ALS patients. The secondary aim was then to compare US diaphragm thickness index (ΔTdi) with a new parameter (ΔTmax index). Methods 41 patients with ALS and 30 healthy subjects were enrolled in the study. All subjects underwent spirometry, SNIP and diaphragm US evaluation, while arterial blood gases were measured in some patients only. US assessed diaphragm thickness (Tdi) at tidal volume (Vt) or total lung capacity (TLC), and their ratio (ΔTmax) were recorded. Changes (Δ) in Tdi indices during tidal volume (ΔTdiVt) and maximal inspiration (ΔTdiTLC) were also assessed. Results ΔTdiTLC (p <0.001) and ΔTmax (p = 0.007), but not ΔTdiVt, differed between patients and controls. Significant correlation (p < 0.05) was found between ΔTdiTLC, ΔTmax and FVC. The ROC curve analysis for comparison of individual testing showed better accuracy with Δtmax than with ΔtdiTLC for FVC (AUC 0.76 and 0.27) and SNIP (AUC 0.71 and 0.25). Conclusion Diaphragm thickness assessed by ultrasound significantly correlates with global respiratory alterations in patients with ALS. ΔTmax represents a new US index of early diaphragmatic dysfunction, better related with the routinely performed lung function tests. This study demonstrates a significant correlation between ultrasound based diaphragm thickness variation and lung impairment in ALS patients. We propose a new ultrasound index of the diaphragm, ΔTmax, which shows a better accuracy than FVC and SNIP test, and that could help clinicians on patient counselling regarding NIV.